Identification of the human-land relationship involved in the urbanization of rural settlements in Wuhan city circle, China. (July 2020) - Zhu, Siyang; Kong, Xuesong; Jiang, Ping
Abstract: The conversion of population and land from rural to urban areas has been widely explored; however, the spatial change in rural settlements and its relations to population changes involved in urbanization have been ignored. This paper aims to reveal the underlying human-land relationship from the perspective of rural settlement urbanization (RSU). Based on identifying the spatiotemporal characteristics of RSU in Wuhan city circle from 2009 to 2016, we analyzed the human-land relations using a combination of a dynamic coupling model and a decoupling model. The results showed that a total area of 27.77 km 2 (accounting for 0.81% of the level in 2009) of rural settlements was converted to urban construction land from 2009 to 2016. Although the rural population decreased by 32.21%, the overall size of rural settlements increased by 104.62 km 2, and 37 counties had a low-level coordination between population urbanization and RSU. Only 2 counties emerged with high-level coordination in this process. Additionally, the changes in rural settlements and rural population showed a strong negative decoupling; that is, the population decreased while the area of rural settlements increased. Combining the decoupling results with the coupling analysis, eight human-land relationship patterns in rural settlement urbanization were identified, and "strong negative decoupling–low-level coupling" was the main pattern observed in counties, which summarized the human-land relations in most RSU and should be given priorities in improving rural human-land relationships. The question of how to promote harmonious human-land relationships lies at the core of promoting balanced urban-rural development. This research could provide a decision-making basis for formulating a sustainable development strategy for urban-rural integration. Highlights: The spatiotemporal characteristics of rural settlement urbanization were analyzed in Wuhan city circle during 2009–2016. A low-level coordination of the human-land relationship was observed in rural settlement urbanization. Eight human-land relationship patterns in rural settlement urbanization were identified. "Strong negative decoupling–low-level coupling" was the most common manifestation in rural settlement urbanization.